Chronic Myeloid Leukemia with cryptic Philadelphia translocation and extramedullary B-lymphoid blast phase as an initial presentation - Soliman, Dina S; Amer, Aliaa M; Mudawi, Deena; Al-Sabbagh, Zafar; Alkuwari, Einas; Al-Sabbagh, Ahmad; Ibrahim, Feryal; Yassin, Mohamed A (Acta Biomedica Atenei Parmensis, 2018)
Chronic Myeloid Leukemia (CML) is a clonal myeloproliferative neoplasm (MPN) characterized by the presence of a reciprocal translocation between the long arms of chromosomes 9 and 22, t(9;22)(q34:q11), resulting in fusion of the break point cluster region (BCR) with the ABL gene, which forms an oncogene, the transcript of which is an oncoprotein with a tyrosine kinase function. In the great majority of CML; BCR/ABL1 is cytogenetically visualized as t(9;22); giving rise to the Ph chromosome, harboring the chimeric gene. Cryptic or masked translocations occur in 2–10% patients with no evidence for the BCR/ABL rearrangement by conventional cytogenetics but are positive by Fluorescence in Situ Hybridization (FISH) and/or reverse transcriptase polymerase chain reaction (RT-PCR). These patients are described as Philadelphia negative (Ph negative) BCR/ABL1- positive CML with the chimeric gene present on the derivative chromosome 22, as in most CML cases, or alternatively on the derivative 9 in rare occasions. In the majority of cases, CML is diagnosed in the chronic phase; it is less frequently diagnosed in accelerated crises, and occasionally, its initial presentation is as acute leukemia. The prevalence of extramedullary blast phase (BP) has been reported to be 7–17% in patients with BP. Surprisingly, no extramedullary blast crises of B- lymphoid lineage have been reported before among cases of CML as the initial presentation. We report an adult male diagnosed as CML- chronic phase when he was shortly presented with treatment-naive extramedullary B-lymphoid blast crises involving multiple lymph nodes, with no features of acceleration or blast crises in the peripheral blood (PB) and bone marrow (BM). In addition the patient had variant/cryptic Philadelphia translocation. This is the first report of CML, on the best of our knowledge, with extramedullary B-lymphoid blast phase, as initial presentation, that showed a cryptic Ph translocation